Optimization of load dispatch strategies for an islanded microgrid connected with renewable energy sources. (15th June 2021) - Fatin Ishraque, Md.; Shezan, Sk. A.; Ali, M.M.; Rashid, M.M.
Highlights: An IHMS for southern divisions of Bangladesh has been designed and optimized. Real time field meteorological data of solar, wind and temperature has been used. The estimation of the reduction of NPC, COE, CO2 emissions have been reported. Voltage, Power and Frequency responses reported considering dispatch strategies. Simulation results from HOMER Pro and MATLAB Simulink have been represented. Sustainable development and uninterrupted power supply assured from the analysis. Abstract: This paper evaluates the design and optimization of an islanded hybrid microgrid for various load dispatch strategies by assessing the optimal sizing of each component, the power system responses and different cost analysis of the microgrid. Four divisions of the northern side of Bangladesh namely, Mymensingh, Rangpur, Rajshahi and Sylhet hybrid microgrids incorporating solar PV, wind turbine, battery storage, diesel generator and a load of 27.31 kW have been optimized for five different dispatch strategies: (i) Load Following, (ii) Cycle Charging, (iii) Generator Order, (iv) Combined Dispatch and (v) HOMER predictive dispatch strategy. The proposed microgrids have been optimized to reduce the Net Present Cost, CO2 emission and Levelized Cost of Energy. All the five dispatch strategies for the four microgrids have been analyzed in HOMER Pro, and subsequently, the power system responses and feasibility analysis of the microgrids have been performed in MATLAB Simulink. The results obtained in this study provide a guideline to estimate component sizes and costs for the optimal operation of the proposed microgrids under various load dispatch scenarios. The simulation results suggest that the Load Following is the best dispatch strategy having the lowest Net Present Cost of 149, 794 USD, Levelized Cost of Energy of 0.204 USD/kWh, Operating cost of 3, 698 USD and CO2 emission of 3, 298 kg/year with a stable power system response. Combined Dispatch is found to be the worst strategy having the maximum Levelized Cost of Energy of 0.532 USD/kWh, Net Present Cost of 415, 030 USD, Operating cost of 15, 394 USD and Green House Gas emissions of 17, 266 kg/year and comparatively poor power system responses. Finally, a brief comparative analysis has been presented between designed microgrid system and other hybrid energy systems and conventional power stations in terms of Levelized Cost of Energy, Net Present Cost, CO2 emissions and operating cost.